A Venturi tube design for studying travelling bubble cavitation. Issue 1 (1st April 2022) - Li, Zehao; Zuo, Zhigang; Qian, Zhongdong
Abstract: Travelling bubble cavitation always appears in forms of nearly spherical travelling bubbles. These bubbles grow from the freestream/surface nuclei in the low-pressure region in the flow channel. As the inception of travelling bubble cavitation is very sensitive to the boundary layer flow, attached cavitation would be likely to appear simultaneously if the flow is not well-controlled. In this study, based on the interaction between cavitation inception and boundary layer, a Venturi tube for studying travelling bubble cavitation is designed with the aid of a computational fluid dynamics (CFD) approach. The flow channel of this Venturi tube is composed of an inlet straight pipe (10 mm × 10 mm square), a contraction section, a throat section (5 mm × 5 mm square) and two diffuser sections (diffuser 1 and diffuser 2). For visualization convenience, each cross section of the Venturi tube is square. From CFD results, no flow separation occurs near the throat section and the adverse pressure gradient is relatively small, which indicates attached cavitation may not occur. The manufactured Venturi tube is installed in a blow-down type tunnel and tested with Reynolds number at roughly 3 - 3.75 × 10 4 and the pressure recovery number at 2.95 - 4.41. The velocity of the Venturi inlet varies from about 6 m/s to 7.5 m/s. Experiment results shows travelling bubble cavitation can be generated successfully and pure travelling bubble cavitation inception is achieved in this Venturi tube. The formation of travelling bubbles is recorded by a Phantom VEO 710L high-speed camera with framing rate of 24000 fps.